PENYULUHAN PENANGANAN KASUS PATAH TULANG EKSTREMITAS UNTUK MASYARAKAT DI INSTALASI RADIOLOGI RSUD KAB. SUMEDANG - Leny Anggraeni (Jurnal Pengabdian Kepada Masyarakat, 2023)
AbstractFracture in medical terms is a loss of continuity of bone tissue which is characterized by pain, swelling, deformity and impaired function at the fracture area, usually caused by trauma to the bone, depending on the type, intensity and direction of the trauma.The most common cause of most fractures is not affected, both work accidents, traffic accidents and so on. The lack of knowledge in handling fracture cases in the community, usually the community will bandage the patient with non-sterile cloth and immediately move the patient to the side of the road without knowing the consequences of complications if done properly will cause fracture complications.The purpose of this PKM is to provide education to patients and the public about the importance of proper handling of fracture cases.Method used is interactive lectures.Results of this PKM are expected to increase public awareness of the importance of proper handling of fracture cases. Keywords :Education, Treatment, Fractures